Emotional constraint, father-son relationships, and men's wellbeing - Cleary, Anne (Frontiers in Sociology, 2022)
Research findings indicate an association between particular practices of masculinity and male suicide and this paper examines early and ongoing gender influences in the lives of men who made a clinically serious suicide attempt in adulthood. The men (n=52) interviewed in this qualitative study were from families where hegemonic ideals of masculinity, emphasising strength and emotional stoicism, prevailed. Fathers were important figures within this system and were instrumental in demonstrating masculinity practices which emphasised male competence and discouraged signifiers of vulnerability. This masculinity environment restricted behaviour and the expression of feeling for males within the family, shaped communication between fathers and sons and affected the father’s ability to emotionally engage with his son. There was an absence of positive, nurturing, relationships between fathers and sons and more usually father-son interaction was antagonistic due to a real or perceived lack of love and care from the father and or his abusive behaviour. Fathers who were emotionally distant, and especially those who were abusive, gave rise to feelings of anger and sadness in their sons and negatively affected their well-being. Constraints on emotional expression and prohibitions on revealing vulnerability denied the men a space to learn about, and cope with, the emotional issues of their lives and prevented them from revealing childhood trauma. Difficulties were usually prolonged into adulthood when these men were vulnerable to situations and events which threatened their psychological security. The prevailing masculinity was contested but participants felt pressure to conform due to expectations within the family and the enforcement of these practices in the neighbourhood. The result was a mutually reinforcing system of emotional constraint within the home and the neighbourhood which was problematic for all and particularly challenging for participants with adverse childhood experiences. Participants coped by sublimating problems and disguising vulnerability, seeking emotional comfort within intimate partnerships and self-medicating with alcohol. Overall, the study revealed ongoing emotions and emotion work and significant challenges to wellbeing for men raised in environments of hegemonic masculinity and emotional restriction.